Case report: Right atrium-inferior vena cava bypass in a patient with unusual cardiac cystic echinococcosis - Liu, Lulu; Wu, Binggang; Li, Mei; Guo, Yingqiang (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular hydatid disease is caused by parasitic infection of Echinococcus granulosus, which could be asymptomatic or life-threatening depending on lesion site, granuloma size and disease progression. Diagnosis and treatment of cardiac echinococcosis should be under comprehensive consideration. In this case, we reported a successful right atrium-inferior vena cava bypass surgery in a 31-year-old female with unresectable right atrial echinococcosis and inferior vena cava obstruction.